2021
DOI: 10.3233/jad-200627
|View full text |Cite
|
Sign up to set email alerts
|

Declining Use of Potentially Inappropriate Medication in People with Dementia from 2000 to 2015: A Repeated Cross-Sectional Nationwide Register-Based Study

Abstract: Background: Studies have shown declining use of potentially inappropriate medication (PIM), medication where risks associated with use outweigh potential benefits in older people. However, the trend in people with dementia remains unknown. Objective: To test the hypothesis that the use of PIM has decreased in people with dementia in line with the declining use in the general older population. Methods: Repeated cross-sectional register-based study of the entire Danish population aged ≥65 years (2000: N = 802,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Of all included studies, 53 studies reported the prevalence of PIM ( Zuckerman et al, 2005 ; Raivio et al, 2006 ; Holmes et al, 2008 ; Chan et al, 2009 ; Lau et al, 2010 ; Somers et al, 2010 ; Tjia et al, 2010 ; Andersen et al, 2011 ; Lau et al, 2011 ; Bosboom et al, 2012 ; Colloca et al, 2012 ; Parsons et al, 2012 ; Thorpe et al, 2012 ; Fiss et al, 2013 ; Koyama et al, 2013 ; Montastruc et al, 2013 ; Toscani et al, 2013 ; Tjia et al, 2014 ; Hanlon et al, 2015 ; Skoldunger et al, 2015 ; Barry et al, 2016 ; Cross et al, 2016 ; Chuang et al, 2017 ; Hyttinen et al, 2017 ; Oesterhus et al, 2017 ; Ramsey et al, 2017 ; Wucherer et al, 2017 ; Kristensen et al, 2018 ; Nguyen et al, 2018 ; Renom-Guiteras et al, 2018 ; Eshetie et al, 2019a ; Bala et al, 2019 ; Brimelow et al, 2019 ; Denholm et al, 2019 ; Eshetie et al, 2020 ; Eshetie et al, 2020 ; Forgerini et al, 2020 ; Murphy et al, 2020 ; Rausch and Hoffmann, 2020 ; Ruangritchankul et al, 2020 ; Delgado et al, 2021 ; Ferreira et al, 2021 ; Jaramillo-Hidalgo et al, 2021 ; Kristensen et al, 2021 ; Vickers et al, 2021 ; Buckley et al, 2022 ; Delgado et al, 2022 ; Rangfast et al, 2022 ; Riedl et al, 2022 ; Yoon et al, 2022 ; Zhao et al, 2022 ; Bae-Shaaw et al, 2023 ; Ryskina et al, 2023 ), and 28 studies reported the prevalence of polypharmacy ( Lau et al, 2010 ; …”
Section: Resultsunclassified
See 1 more Smart Citation
“…Of all included studies, 53 studies reported the prevalence of PIM ( Zuckerman et al, 2005 ; Raivio et al, 2006 ; Holmes et al, 2008 ; Chan et al, 2009 ; Lau et al, 2010 ; Somers et al, 2010 ; Tjia et al, 2010 ; Andersen et al, 2011 ; Lau et al, 2011 ; Bosboom et al, 2012 ; Colloca et al, 2012 ; Parsons et al, 2012 ; Thorpe et al, 2012 ; Fiss et al, 2013 ; Koyama et al, 2013 ; Montastruc et al, 2013 ; Toscani et al, 2013 ; Tjia et al, 2014 ; Hanlon et al, 2015 ; Skoldunger et al, 2015 ; Barry et al, 2016 ; Cross et al, 2016 ; Chuang et al, 2017 ; Hyttinen et al, 2017 ; Oesterhus et al, 2017 ; Ramsey et al, 2017 ; Wucherer et al, 2017 ; Kristensen et al, 2018 ; Nguyen et al, 2018 ; Renom-Guiteras et al, 2018 ; Eshetie et al, 2019a ; Bala et al, 2019 ; Brimelow et al, 2019 ; Denholm et al, 2019 ; Eshetie et al, 2020 ; Eshetie et al, 2020 ; Forgerini et al, 2020 ; Murphy et al, 2020 ; Rausch and Hoffmann, 2020 ; Ruangritchankul et al, 2020 ; Delgado et al, 2021 ; Ferreira et al, 2021 ; Jaramillo-Hidalgo et al, 2021 ; Kristensen et al, 2021 ; Vickers et al, 2021 ; Buckley et al, 2022 ; Delgado et al, 2022 ; Rangfast et al, 2022 ; Riedl et al, 2022 ; Yoon et al, 2022 ; Zhao et al, 2022 ; Bae-Shaaw et al, 2023 ; Ryskina et al, 2023 ), and 28 studies reported the prevalence of polypharmacy ( Lau et al, 2010 ; …”
Section: Resultsunclassified
“…The sample size ranged from 34 to 259,291, comprising a total of 658,431 study subjects. Most studies (n = 30) were conducted in Europe(Raivio et al, 2006;Andersen et al, 2011;Colloca et al, 2012;Parsons et al, 2012;Fiss et al, 2013;Montastruc et al, 2013;Toscani et al, 2013; Skoldunger et al, 2015;Barry et al, 2016;Hyttinen et al, 2016;Walsh et al, 2016;Clague et al, 2017;Kanagaratnam et al, 2017;Oesterhus et al, 2017;Wucherer et al, 2017;Kristensen et al, 2018;Renom-Guiteras et al, 2018;Denholm et al, 2019;Kristensen et al, 2019;Soysal et al, 2019;Murphy et al, 2020;Rausch and Hoffmann, 2020;Delgado et al, 2021;Gareri et al, 2021;Jaramillo-Hidalgo et al, 2021;Kristensen et al, 2021;Buckley et al, 2022;Delgado et al, 2022;Rangfast et al, 2022;Riedl et al, 2022), only two studies were…”
mentioning
confidence: 99%
“…3 In a Danish population, the broader issues of potentially inappropriate medication (PIM) use was examined through a population-based register. 4 PIM can include inappropriate drug choice, polypharmacy, or potential drug-drug interactions, but generally refers to medications that should be avoided in older people due to the potential risks outweighing the benefits. Although the use of PIM decreased from 2000 to 2015 (from 54.7% to 43.5% in people with dementia and from 39.5% to 28.8% in people without dementia), there remained a high prevalence of potentially inappropriate prescribing practices, including in patients with dementia.…”
mentioning
confidence: 99%
“…Although the use of PIM decreased from 2000 to 2015 (from 54.7% to 43.5% in people with dementia and from 39.5% to 28.8% in people without dementia), there remained a high prevalence of potentially inappropriate prescribing practices, including in patients with dementia. 4 While the term polypharmacy indicates the administration of multiple medications in a patient, there is no consensus definition. A systematic review of polypharmacy definitions categorized them as "(1) numerical only (using the number of medications to define polypharmacy), (2) numerical with an associated duration of therapy or health care setting (such as during hospital stay), or (3) descriptive (using a brief description to define polypharmacy)."…”
mentioning
confidence: 99%
See 1 more Smart Citation